Association between physical exercise and innovative behavior among university students: the mediating role of learning engagement - Yang, Meiyuan; Lin, Ye; Liu, Dongmei; Zhen, Wanpeng; Jin, Yongchao; Yan, Sihan; Li, Yang; Chen, Jianwei (Frontiers in Psychology, 2026)
PurposeThis study examined the relationship between physical exercise and innovative behavior in university students, with a particular focus on the mediating role of learning engagement. The findings aimed to provide insights for fostering innovative talents and enhancing the quality of talent development in higher education.MethodsBy means of convenient sampling, a total of 1,176 students were recruited from a comprehensive university in North China to participate in the online survey. This study employed the physical exercise scale, the learning engagement scale, and the innovative behavior scale as the main tools. The data were analyzed using SPSSAU, and descriptive statistics, correlation analysis, regression analysis and tests were employed to examine the mediating role of learning engagement.Results(1) There was no significant gender difference in learning engagement and innovative behavior among college students (p > 0.05); In terms of physical exercise, there was a significant gender difference (p < 0.05). (2) Physical exercise is positively correlated with college students’ innovative behavior (r = 0.435, p < 0.01), positively correlated with learning engagement (r = 0.524, p < 0.01), and learning engagement was positively correlated with innovative behavior (r = 0.314, p < 0.01). Physical exercise has a significant direct effect on innovative behavior, explaining 72.6% of the variance. Learning engagement plays a mediating role between physical exercise and innovative behavior, with an effect value of 27.4%.Conclusion(1) The research results revealed a significant interrelationship among physical exercise levels, learning engagement and innovative behaviors among college students. (2) Physical exercise was a significant predictor of innovative behavior and further indirectly influences it through the mediating role of learning engagement.